2016
DOI: 10.1097/ajp.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

Time to Onset of Sustained Postoperative Pain Relief (SuPPR)

Abstract: Objectives Prior work on postoperative pain trajectories have examined pain score changes over time using daily averages of pain scores. However, little is known about the time required until patients consistently report minimal postoperative pain. Materials and Methods We conducted a retrospective cohort study of surgical case data from 7,293 adult patients to examine the impact of age, gender, and the type of surgery on the time to sustained postoperative pain relief (SuPPR). We defined SuPPR as the time r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…1; [47]). Der Zeitraum bis zum Einsetzen einer anhaltenden Schmerzlinderung gilt daher auch als wichtige Evaluierungsgröße für die Qualität des postoperativen Schmerzmanagements [137,153].…”
Section: Risikofaktoren Für Die Entwicklung Chronischer Postoperativeunclassified
“…1; [47]). Der Zeitraum bis zum Einsetzen einer anhaltenden Schmerzlinderung gilt daher auch als wichtige Evaluierungsgröße für die Qualität des postoperativen Schmerzmanagements [137,153].…”
Section: Risikofaktoren Für Die Entwicklung Chronischer Postoperativeunclassified
“…A further drawback is that the study was not designed to examine the later phase of recovery, beyond day 3. Previous research has shown that the usual postoperative pain trajectory decreases during the few days after surgery, 25,26 thereby supporting measuring acute postoperative recovery during the first few days. However, it is possible to have a slight increase of pain when patients start to mobilize after surgery.…”
Section: Limitationsmentioning
confidence: 85%
“…In fact, a large proportion of patients have pain scores that remain the same or even increase with time. Recent studies have demonstrated that age, gender, type of surgery, and preoperative chronic opioid use influences the postoperative pain course [39, 40]. …”
Section: Personalized Carementioning
confidence: 99%